Pentingnya Etika Komunikasi Dalam Memperkuat Organisasi Tinjauan Agama Islam - Bagaz Eka Nurdiansyah; Adam Maulana Syahadji; Ismail Mubarok (Student Scientific Creativity Journal, 2024)
Islamic communication styles outline a number of principles that teach us how to communicate with other people.This hinders the use of appropriate language, which is clear, concise, and respectful of others.In Islam, true communication is based on the concept of "husnul khotimah," or sincere reflection.These principles can be applied in an organizational context to strengthen ties between team members and external parties.For example, it's important to use sharp and smooth tools and to avoid using words that hurt other people's feelings.In addition, communication skills are highly valued in Islam.That is to say, it does not only convey the message but also hinder the dissemination of information about palm oil or fitnah.Maintaining open communication is also important; this means describing what we say, how we say it, and how we convey it.In an organizational context, Islamic principles-based communication techniques can strengthen trust and productive.